On the Influence of Enso And IOD on Rainfall Variability Over The Musi Basin, South Sumatra - Wijaya Mardiansyah; Dedi Setiabudidaya; M. Yusup Nur Khakim; Indra Yustian; Zulkifli Dahlan; Iskhaq Iskandar (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
The southern Sumatera region experiences one rainy season and one dry season in a year associated with seasonal change in monsoonal winds. The peak of rainy season is occurring in November-December-January during the northwest monsoon season, while the dry season comes in June-July-August during the southeast monsoon season. This study is designed to evaluate possible influence of the coupled ocean-atmospheric modes in the tropical Indo-Pacific region, namely the El Niño-Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) on the rainfall variability over the catchment area of the Music Basin, South Sumatera. The ENSO and IOD occurrences were reflected by the variability of sea surface temperature (SST) in the tropical Pacific and Indian Ocean, respectively. During El Niño and/or positive IOD episode, negative SST anomalies cover the eastern tropical Indian Ocean and western tropical Pacific including the Indonesian seas, leading to suppress convective activities that result in reduce precipitation over the maritime continent. The situation is reversed during La Niña and/or negative IOD event. The results revealed that the high topography area (e.g. Bukit Barisan) was shown to be instrumental to the pattern of rainfall variability. During the 2010 negative IOD co-occurring with La Niña event, the rainfall was significantly increase over the region. This excess rainfall was associated with warm SST anomaly over the eastern tropical Indian Ocean and the Indonesian seas. On the other hand, extreme drought event tends to occur during the 2015 positive IOD simultaneously with the occurrence of the El Niño events Investigation on the SST patterns revealed that cold SST anomalies covered the Indonesian seas during the peak phase of the 2015 positive IOD and El Niño event.